Penggunan Ethepon untuk Peningkatan Hasil dan Ukuran Rimpang Jahe (Zingiber officinale Rosc.) Var. Badak - Joedojono Wiroatmodjo (Jurnal Ilmu Pertanian Indonesia, 1991)
Attempt to increase yield of 4-6 month old exportable ginger was tested by ethepon applications. This experiment was carried out at IPB Experimental Station Tajur from November 1988 - May 1989, with rates of application of 0, 10000, 20000, 30000, and 40000 ppm by volume. Sprayed plots were combinations of rice husk mulching (0 dan 5 ton/ha) and N fertilizations of 0,200 and 400 kg N/ha. Except for tuber weight and total production, the growth parameters were not influenched by ethepon. The best application of 10000 ppm markedly increased the fresh tuber weight by 91,8% per hill or 81,3% of the total yield.